OC-037 Clinical outcomes and risk of lymph node metastases in patients with t1b oesophageal adenocarcinoma. (17th June 2017) - Sever, N; Lovat, L; Atherton, RR; Mitchison, M; rodriguez-Justo, M; Alzoubaidi, D; novelli, M; Haidry, R
Abstract : Introduction: Oesophageal adenocarcinoma (OAC) carries a poor prognosis compared to other gastrointestinal tract tumours. Advances in minimally invasive endoscopic therapy can provide curative intervention of early OAC arising in Barrett's oesophagus (BE). Historically, patients with OAC and submucosal involvement (T1b) were offered surgery due to risk of lymph node metastases (LNM). Endoscopic resection (ER) is a viable alternative to surgery in T1b tumours with low risk (LR) histopathological features. Aim: To assess the overall risk of LNM and long-term outcomes of patients with LR and high risk (HR) T1b OAC. Method: All patients with T1b OAC on endoscopic resection specimens at a single centre during 2008–2015 were included, with no sign of metastatic disease. All specimens were reviewed by two expert histopathologists. LR tumour was defined as completely resected, well or moderately differentiated, with only superficial submucosal involvement (<500 µm) and no lymphovascular invasion. HR tumour was defined by incomplete excision, poorly differentiation, deep submucosal infiltration (>500 µm) or lymphovascular invasion. Disease was considered metastatic if there was lymph node involvement in surgical resection specimens or advanced OAC on follow-up. Results: 59 patients with T1b OAC on ER specimens were included: 13 (22%) had LR and 46 (78%) HR tumours. In total 37 patients were treated conservatively (12 LR, 25 hour) and 22 patients (37%) underwent oesophagectomy (1 LR, 21 hour). There was no surgery-related mortality. After a median follow-up of 38 months (range 12–87) no patients with LR OAC developed metastatic disease. Ten of the 46 hour patients (22%) developed metastatic disease at latest follow up; 4 of these had LNM in surgical resection specimens and 6 had metastatic disease detected on follow-up. In the HR group that were treated conservatively compared to those treated with surgery, although a trend was observed towards better survival in the surgery group, there was no statistically significant long-term survival benefit (log rank p=0.22). Conclusion: Our results show rate of LNM in T1b OAC with LR histopathological features to be very low and endoscopic treatment in these patients is preferred to surgery. HR T1b cancers in our series carry a significant lymph node metastases risk of 22%. In selected HR patients in whom surgery may not be an option, a conservative approach is a valid alternative but rigorous follow-up is required due to the risk of LNM. Disclosure of Interest: None Declared